QUIET HIRING RECONCEPTUALIZED: INTERNAL TALENT MARKETPLACES AND THE FUTURE OF STRATEGIC WORKFORCE PLANNING - Hairyzal; Ramon Zamora; Oktavianti (RADJA PUBLIKA, 2026)
This article reconceptualizes quiet hiring as a strategic approach to workforce management supported by internal talent marketplaces (ITMs) and strategic workforce planning (SWP). As organizations face increasing pressure to adapt to rapid technological change and talent shortages, traditional hiring models are becoming less effective. Using a narrative review methodology, the study synthesizes existing literature on quiet hiring, ITMs, and skills-based workforce strategies. The findings suggest that quiet hiring, when supported by AI-driven platforms, can evolve from an ad hoc practice into a structured mechanism for internal talent deployment. ITMs enable real-time skills matching, enhance workforce agility, and improve employee career mobility. However, challenges related to governance, transparency, and equity remain critical considerations. The study highlights the importance of integrating ITMs into SWP processes to support data-driven decision-making and scenario planning. It also emphasizes the need for organizational readiness, including capability development and ethical oversight. Overall, the article contributes to both theory and practice by offering a strategic framework for leveraging internal talent in a rapidly changing work environment.